SPECIAL REVERSE VALVE OF THE RACK FOR THE DURABILITY TESTS OF HIGH-PRESSURE HOSES - Muliar, Yu. I. (Visnyk of Vinnytsia Politechnical Institute, 2015)
The construction of the special reverse valve of the rack for the durability tests of high-pressure hoses in the pulse-mode of loading and its mathematical model that allows getting equalization of static descriptions of valve are considered in the paper.